Fiscal policy in the smaller industrial countries, 1972-82 - Blöndal, Gísli, 1935- (International Monetary Fund, 1986)
This study was undertaken to provide information and analyses of developments in the public finances of the smaller industrial countries over the decade 1972-82. It also reflects an evolving pattern in the fiscal Affairs Department of the International Monetary Fund of following fiscal developments in groups of member countries. At the same time, the study is intended to partially meet recent requests of the Executive Board for international comparison and anlysis of various aspects of fiscal developments and policies. The choice of countries was made on the basis of two criteria: first, the availability of statistical and other sources suitable for comparative purpose; and secon, the considerable gap in the literature on comparative fiscal policies in these countries, much more than in the major industrial countries-only other homogenous group of member countries that meets the first criterion.